The time of my life - Ahern, Cecelia (London : Harper Collins Publishers, 2016)
Lucy Silchester is. She's busied herself with other stuff: friends lives, work issues, her deteriorating car, that kind of thing. But shes stuck in a rut - and deluding everyone. Only Lucy knows the real truth.
Keywords: Conduct of life -- Fiction